2020
DOI: 10.3233/jad-200425
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Acetylcholinesterase Inhibitors Induce Differentiation and Neuritogenesis in Neuronal Cells in vitro Through Activation of the AKT Pathway

Abstract: Background: Alzheimer’s disease (AD) is characterized by a progressive loss of episodic memory associated with amyloid-β peptide aggregation and the abnormal phosphorylation of the tau protein, leading to the loss of cholinergic function. Acetylcholinesterase (AChE) inhibitors are the main class of drugs used in AD therapy. Objective: The aim of the current study was to evaluate the potential of two tacrine-donepezil hybrid molecules (TA8Amino and TAHB3), which are AChE inhibitors, to induce neurodifferentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…In previous studies, it was demonstrated that the donepezil–tacrine hybrid compound (TA8Amino) showed a potent allosteric modulator of AChE and induced promising effects in terms of neuroprotection and neurodifferentiation [ 32 , 38 ]. These studies highlight that TA8Amino demonstrated low toxicity and a potent inhibitory effect on AChE at lower concentrations than donepezil and tacrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was demonstrated that the donepezil–tacrine hybrid compound (TA8Amino) showed a potent allosteric modulator of AChE and induced promising effects in terms of neuroprotection and neurodifferentiation [ 32 , 38 ]. These studies highlight that TA8Amino demonstrated low toxicity and a potent inhibitory effect on AChE at lower concentrations than donepezil and tacrine.…”
Section: Discussionmentioning
confidence: 99%
“…For AChEIs-induced neuronal differentiation assays, the same protocol was performed (except for the addition of RA). The analysis of the percentage of neuronal differentiation and neurite outgrowth was performed according to a previous protocol [ 38 ]. Briefly, a total of 20 photographs (20× magnification) were taken of each group treatment using an inverted phase microscope (Zeiss, Jena, Germany) to quantify the percentage of differentiated cells and neurite size; the ImageJ software (Fiji, image processing package) and the Simple Neurite Tracer plugin were used for these measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of PTEN in AD mouse models is associated with several consequences, such as reduced expression of Bax protein, decreased apoptosis, lower levels of DNA fragmentation, reduced endoplasmic reticulum stress [ 130 ], and rescue of normal synaptic function and cognition [ 131 ]. Noteworthy, reduced activation of PTEN and increased AKT phosphorylation might be involved in neuritogenesis and neurodifferentiation [ 84 ]. Accordingly, targeting PTEN to induce AKT activation might be a potential approach to be investigated in AD therapy ( Fig.…”
Section: Pi3k/akt Pathway Mediating the Multi-target Effects In Admentioning
confidence: 99%
“…Foram desenvolvidos então dois compostos (TA8Amino e TAHB3) que demonstraram eficiência superior aos compostos originais com relação à inibição da AChE (Chierrito et al, 2017;Moreira et al, 2020) Figura 2: Representação das estruturas moleculares dos compostos AChEIs com seus respectivos valores de 50% da ação inibitória máxima (IC50). Compostos originais donepezila e tacrina e os novos compostos híbridos TAHB3 e TA8Amino (dados extraídos de Chierrito, et al, 2017).…”
Section: Novos Compostos Acheis Para O Tratamento Da Daunclassified
“…Os resultados já obtidos demonstraram que, por meio da ativação da via PI3K/Akt (do inglês, phosphoinositide 3-kinase e Protein Kinase B), os compostos estimularam a neurodiferenciação e neuritogênese nas células SH-SY5Y; os compostos também demonstraram baixos níveis de citotoxicidade e não induziram alterações na viabilidade celular nas concentrações próximas ao IC50 de inibição da AChE. Também foi observado um efeito neuroprotetor em resposta a danos induzidos pelo peptídeo Aβ (Moreira, 2019;Moreira et al, 2020). Esses dados preliminares demonstram o potencial terapêutico dos compostos TA8Amino e TAHB3 para DA, e ressaltam a importância da continuação de estudos com essas moléculas em diferentes modelos e linhagens celulares para comprovar a capacidade indutora de diferenciação e de efeitos neuroprotetores 1.5.…”
Section: Novos Compostos Acheis Para O Tratamento Da Daunclassified